BIOMEDICAL POTENTIAL OF MARINE CYANOBACTERIA - Lik Tong Tan (JOURNAL OF COASTAL DEVELOPMENT, 2006)
Cyanobacteria, in particular those found living in the ocean, are emerging as an importantsource of unique bioactive secondary metabolites. A plethora of natural products, mostly nitrogencontainingmolecules, have been reported with majority belonging to the polyketide synthase (PKS)and/or non-ribosomal polypeptide synthetase (NRPS) structural class. Curacin A and the dolastatinsare examples of important marine cyanobacterial metabolites possessing exquisite anticancerproperties. Genetic studies on the biosynthetic capacity of these marine microalgae revealed manynovel biochemical features pertaining to the enzymology of secondary metabolism. Biodiscovery ofmarine cyanobacteria for new therapeutic agents as well as harnessing its biosynthetic gene clustersrepresent an exciting and fruitful area of research in marine biotechnology.